Synthetic chiral light for efficient control of chiral light–matter interaction - Ayuso, David; Neufeld, Ofer; Ordonez, Andres F.; Decleva, Piero; Lerner, Gavriel; Cohen, Oren; Ivanov, Misha; Smirnova, Olga (Nature Photonics, 2019)
Light is a very powerful and precise tool, allowing us to control1, shape2,3 and create new phases4 of matter. In such tasks, the magnetic component of a light wave is essential in defining the wave’s helicity, but it influences the optical response of matter only weakly. Chiral molecules offer a typical example, in which the weakness of magnetic interactions hampers our ability to control the strength of their chiro-optical response5, limiting it at several orders of magnitude below the full potential. Here, we introduce and theoretically analyse a new type of chiral light: freely propagating, locally and globally chiral electric fields, which interact with chiral matter extremely efficiently. We show that this synthetic chiral light enables full control over the intensity, polarization and propagation direction of the nonlinear enantio-sensitive optical response of randomly oriented chiral molecules. This response can be quenched or enhanced at will in a desired enantiomer, opening up efficient ways to control chiral matter and for ultrafast imaging of chiral dynamics in gases, liquids and solids.
CRIS-Team Scopus Importer:2023-04-20